Multivariate Analysis of Traumatic Brain Injury: Development of an Assessment Score - Buonora, John E.; Yarnell, Angela M.; Lazarus, Rachel C.; Mousseau, Michael; Latour, Lawrence L.; Rizoli, Sandro B.; Baker, Andrew J.; Rhind, Shawn G.; Diaz-Arrastia, Ramon; Mueller, Gregory P. (Frontiers in Neurology, 2015)
Important challenges for the diagnosis and monitoring of mild traumatic brain injury (mTBI) include the development of plasma biomarkers for assessing neurologic injury, monitoring pathogenesis and predicting vulnerability for the development of untoward neurologic outcomes. While several biomarker proteins have shown promise in this regard, used individually, these candidates lack adequate sensitivity and/or specificity for making a definitive diagnosis or identifying those at risk of subsequent pathology. The objective for this study was to evaluate a panel of six recognized and novel biomarker candidates for the assessment of TBI in adult patients. The biomarkers studied were selected on the basis of their relative brain-specificities and potentials to reflect distinct features of TBI mechanisms including: neuronal damage assessed by neuron-specific enolase (NSE) and brain derived neurotrophic factor (BDNF); oxidative stress assessed by peroxiredoxin 6 (PRDX6); glial damage and gliosis assessed by glial fibrillary acidic protein (GFAP) and S100 calcium binding protein beta (S100b); (4) immune activation assessed by monocyte chemoattractant protein 1/chemokine (C-C motif) ligand 2 (MCP1/CCL2); and disruption of the intercellular adhesion apparatus assessed by intercellular adhesion protein-5 (ICAM-5). The combined fold changes in plasma levels of PRDX6, S100b, MCP1, NSE and BDNF resulted in the formulation of a TBI assessment score (TBIAS) that identified mTBI with a receiver operator characteristic area under the curve of 0.97, when compared to healthy controls. This research demonstrates that a profile of biomarker responses can be used to formulate a diagnostic score that is sensitive for the detection of mTBI. Ideally, this multivariate assessment strategy will be refined with additional biomarkers that can effectively assess the spectrum of TBI and identify those at particular risk for developing neuropathologies as consequence of a mTBI event.